(untitled) (Philological Studies, 2019)
The need for a public announcement of its existence and expressing their own power leads individuals to test it on the walls express their inner concerns via text or images. Graphite (the Greek word grafo and Italian word graffito) is carved, lettering or drawing on a wall or other surface. In words and pictures, with the stylus, paint, spray creates sentences, slogans, pictures and figures, usually witty and spiteful content. They are characterized by the appearance of almost exclusively in urban areas is not Mostar’s urban environment is no exception to this rule. It is in recent years the phenomenon of graffiti and their printing years commonplace. The paper presents the results of research and writing Mostar’s text graphite. The study was conducted continuously since 2006. until 2011. and was repeated in 2016. Presume that view of graffiti gives true insight into the life of the city and the lives of citizens, because the media is not moderated absolutely no aesthetic or cultural norms. In Mostar’s graffiti face of love, political or ethnic, fan, comedy, social, sexual-free, educational, friendly, religious and worldview topics and are thus and Mostar’s graffiti and medium of expression of the public, especially younger urban population.